Plasma EVs Display Antigen-Presenting Characteristics in Patients With Allergic Rhinitis and Promote Differentiation of Th2 Cells - Fang, Shu-Bin; Zhou, Zhi-Rou; Peng, Ya-Qi; Liu, Xiao-Qing; He, Bi-Xin; Chen, De-Hua; Chen, Dong; Fu, Qing-Ling (Frontiers in Immunology, 2021)
Background: Allergic rhinitis (AR) is characterized by IgE-mediated mucosa response after exposure to allergens. Extracellular vesicles (EVs) are nano-size vesicles containing biological cargos for intercellular communications. However, the role of plasma EVs in pathogenesis of AR remains largely unknown. Methods: Plasma EVs from patients with AR were isolated, quantified and characterized. The expression of Der p 1 and antigen-presenting molecules on EVs were determined by western blot, flow cytometry or ELISA. PKH26- and CFSE (carboxyfluorescein succinimidyl ester)-stained AR-EVs were used to determine the uptake of EVs by CD4+T cells and their effects on CD4+T cell proliferation, respectively. Results: Plasma EVs in healthy control (HC) and AR patients showed similar characteristics on the concentration, structural lipid-bilayer and positive for specific EV markers. However, the levels of Der p 1 on plasma EVs from both moderate and severe AR (S-AR) patients were significantly higher than that on HC. The levels of antigen presenting molecules on plasma EVs were similar from three subjects. Moreover, levels of Der p 1 on EVs in plasma, but not nasal secretion, were significantly associated with the symptom score of AR patients and level of plasma IL-13. Additionally, plasma EVs from patients with AR promoted the development of Th2 cells, while no effect was found on CD4+ T cells proliferation. Conclusions: Plasma EVs derived from patients with AR exhibited antigen presenting characteristics and promoted differentiation of Th2 cells, thus providing novel understanding of the pathogenesis of AR.